Student Participation in Online Content-Related Discussion and Its Relation to Students' Background Knowledge - Miikka Turkkila; Henri Lommi (MDPI AG, 2020)
This paper presents two novel network methods developed for education research. These methods were used to investigate online discussions and the structure of students' background knowledge in a blended university course for pre-service teachers (n = 11). Consequently, these measures were used for correlation analysis. The social network analysis of the online discussions was based on network roles defined using triadic motifs instead of more commonly used centrality measures. The network analysis of the background knowledge is based on the Katz centrality measure and Jaccard similarity. The results reveal that both measures have characteristic features that are typical for each student. These features, however, are not correlated when student participation is controlled for. The results show that the structure and extension of a student's background knowledge does not explain their activity and role in online discussions. The limitations and implications of the developed methods and results are discussed.